The Relationship Between Training And Entrepreneurial Activities By Teenage Dropouts At Aisle 4 Tourist Attraction - Novita Wahyuni Nasution; Jamaris Jamaris (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
The study is set against the background of the success of teenage dropouts in trepreneurial activities that are thought to be the result of excellent training. The study is aimed at knowing the training, entrepreneurial activities and revealing the training relationship to the out and go activities of young dropouts. The observation of the writer takes place in aisle 4 tourist attraction. The study uses a quantitative approach with a correlational method. The population in this study is all in trainees in November 2020. This research sample was taken using a random sampling cluster. Data collection techniques using angkets and data analysis techniques using percentage formulas and spreman rho formulas. The result showed that the training performance was categorized as good, that entrepreneurial activities were categorized as good and there was a significant relationship between training and entrepreneurial activities by dropout teenagers. The suggestion from this reseach is that it is hoped that school dropouts will learn more about entrepreneurial activities to dedvelop their entrepreneurship and create new things about entrepreneurship. Keywords: Training, entrepreneurial activities